Bark-Water Interactions Across Ecosystem States and Fluxes - Van Stan, John T.; Dymond, Salli F.; Klamerus-Iwan, Anna (Frontiers in Forests and Global Change, 2021)
To date, the perspective of forest ecohydrologists has heavily focused on leaf-water interactions – leaving the ecohydrological roles of bark under-studied, oversimplified, or omitted from the forest water cycle. Of course, the lack of study, oversimplification, or omission of processes is not inherently problematic to advancing ecohydrological theory or operational practice. Thus, this perspective outlines the relevance of bark-water interactions to advancing ecohydrological theory and practice: (i) across scales (by briefly examining the geography of bark); (ii) across ecosystem compartments (i.e., living and dead bark on canopies, stems, and in litter layers); and, thereby, (iii) across all major hydrologic states and fluxes in forests (providing estimates and contexts where available in the scant literature). The relevance of bark-water interactions to biogeochemical aspects of forest ecosystems is also highlighted, like canopy-soil nutrient exchanges and soil properties. We conclude that a broad ecohydrological perspective of bark-water interactions is currently merited.